Web Quality in Lithuanian Financial Institution: a Comparison with the EU Results - Bonsón-Ponte, Enrique; Cortijo-Gallego, Virginia; EscobarRodriguez, Tomás (Ekonomika, 2008)
The objective of this paper is to analyse the navigation quality of the websites of Lithuanian banks. Information completeness for investors ensures the correct functioning of capital markets. In banking environments, this goal is reached by increasing the use of the corporate Website. For this reason, to ensure the quality of these online resources is one of the most important challenges for central banks and financial authorities. The content of the corporate Websites is being regulated by the Basel II initiatives, but navigation quality is not being observed by regulators. Since this variable has a significant impact on the quality of a web site and can generate competitive advantages, it is necessary to analyse the current practices of financial entities.Financial institutions located in Lithuania find themselves in a rather special situation because the entry of this country into the EU means that they have to adapt to a new cultural environment and incorporate its symbols, rules, institutionalized beliefs and normative systems. One of these is the need to adopt transparent reporting practices in consonance with the rest of European countries. Therefore, the navigation quality in Lithuanian banks is analysed in this paper, the entity size is also considered as a possible variable of explanation, and a comparison with EU result is made, in order to detect competition disadvantages. To reach this goal, each website of the main Lithuanian financial entities is rated on the basis of a series of metrics that measure the quality of navigation, in accordance with the Web Quality Model developed by Calero et al. (2005).Our results show that Lithuanian financial entities are aware of the importance of online resources because the quality of navigation of their websites is high compared with the results reached by the European sample. As a consequence of this fact, it can be concluded that the Lithuanian financial sector is correctly prepared to confront the challenge of the EU framework.